The Influencing Factors for Anxiety Among Fifth-Year Medical Students During Exam Periods at The Faculty of Medicine, University of Zawia - Sobhia Draibi; Hala Araibi; Fatma Alatrag; Ebtehal Eshiak; Aida Belag (AlQalam Journal of Medical and Applied Sciences, 2025)
Exam periods are known to induce significant stress and anxiety among medical students, potentially affecting both their psychological well-being and physiological health. This study aimed to investigate the influencing factors for anxiety during exam periods, with a focus on physiological responses (blood pressure and heart rate) and demographic factors such as gender, age, family history of hypertension (HTN), and daily internet use. A cross-sectional study was conducted with 70 medical students in the fifth year of the Faculty of Medicine at Zawia University (ZU). Physiological parameters, including diastolic and systolic blood pressure and heart rate, were measured before and after the exam. Anxiety levels were assessed using the Zung Self-Rating Anxiety Scale (SAS). The study revealed statistically significant decreases in diastolic blood pressure, systolic blood pressure, and heart rate after the exam period. Female students reported significantly higher stress levels compared to males and were more likely to experience mild to moderate and moderate to severe anxiety. Age was significantly associated with exam anxiety, with students aged 25 and above showing higher anxiety levels. Daily internet use and family history of HTN did not show significant associations with anxiety levels. Exam periods induce measurable physiological stress responses in medical students, with significant reductions in blood pressure and heart rate post-exams. Gender and age are critical factors influencing anxiety levels, with female students and older students experiencing higher stress.